The last 100 days of Abacha : political drama in Nigeria under one of Africa's most corrupt and brutal military dictatorships - Adeniyi, Olusegun (Lagos, Nigeria : Bookhouse Company, 2005)
This book is about the political drama in Nigeria under one of Africa's most corrupt and brutal military dictatorships.
oif 27/01/15; 08/04/15
Loan
Keywords: Abacha, Sani; Authotitarian government; Military government; Nigeria